Changes in Ki-67 Labeling Indices During Neoadjuvant Chemotherapy for Advanced Ovarian Cancer Are Associated With Survival. Issue 4 (1st May 2010) - Pölcher, Martin; Friedrichs, Nicolaus; Rudlowski, Christian; Fimmers, Rolf; Keyver-Paik, Mignon-Denise; Kübler, Kirsten; Sauerwald, Axel; Büttner, Reinhard; Kuhn, Walther; Braun, Michael
Abstract : Objective: To evaluate changes in Ki-67 expression during neoadjuvant chemotherapy (NACT) in advanced ovarian cancer. Materials and Methods: Patients with International Federation of Gynecology and Obstetrics stage IIIC or IV and large-volume ascites were treated with NACT within a phase 2 trial. The expression of Ki-67 was evaluated by immunohistochemistry on paraffin-embedded tissue samples and classified by percentage of stained cells. Survival curves were plotted using the Kaplan-Meier method. Results: Comparison of 40 individual paired results from pretreatment and posttreatment samples revealed a median difference of −0.11 in the Ki-67 index (95% confidence interval, −0.20 to −0.01; P = 0.005, signed rank test). Univariate analysis identified a high Ki-67 index as well as an increasing Ki-67 index after NACT as significant prognostic markers for progression-free survival ( P = 0.004 and P = 0.001; log-rank test). Six of 12 patients with an increased Ki-67 index after NACT developed recurrence within 6 months after therapy. Conclusions: Changes of the Ki-67 index during NACT are associated with progression-free survival. If confirmed in prospective trials, an increasing Ki-67 index during preoperative treatment may serve as an indicator for resistance to chemotherapy.